Determinant of Indonesian Stock Market’s Volatility During the Covid-19 Pandemic - Nugroho, Ainine Devara; Robiyanto, Robiyanto (University of Merdeka Malang, 2021)
The aim of this study is to examine variables that influenced the Jakarta Composite Index (JCI) volatility during the outbreak of COVID-19. The independent variables that are used are gold return volatility and USD/IDR return volatility. This analysis uses daily-time series data which are divided into three periods, those are; before the pandemic (January 2019-August 2019), during the pandemic (January 2020-August 2020), and from January 2019 through August 2020. The method that is used in this study is GARCH analysis in order to dodge data abnormality and heteroscedasticity. Before conducting GARCH analysis, unit root and normality test are conducted to know if the data are stationaries and to decide which GARCH distribution is the most suitable for the data analysis (Gaussian, t-student, or GED distribution). It is proven in this study that during the COVID-19 pandemic, gold return volatility positively affected the JCI volatility and USD/IDR volatility negatively affected JCI volatility. This research can be used as a consideration for investors in choosing their investment during the pandemic or financial crisis by examining gold and USD/IDR volatility effect on JCI volatility.DOI: https://doi.org/10.26905/jkdp.v25i1.4980